50 Jahre Aktiengesetz - Fleischer, Holger; Koch, Jens, 1971-; Kropff, Bruno; Lutter, Marcus
On the 50th anniversary of the German Stock Corporation Act, which was originally ratified in 1965, leading legal scholars met at the birthplace of the law in Bonn to discuss current pressing challenges in this area of law. The results of the discussion, assembled in these conference proceedings, extend far beyond the confines of stock corporation law -- Preface.
Keywords: Germany. -- Aktiengesetz 1965 -- Congresses.; Aktiengesetz 1965 (Germany); Corporation law -- Germany -- Congresses.; Stock companies -- Germany -- Congresses.; Corporation law.; Stock companies.; Germany.; Electronic books.; Conference papers and proceedings.